2023
DOI: 10.1021/acs.biomac.3c00536
|View full text |Cite
|
Sign up to set email alerts
|

Photocuring and Gelatin-Based Antibacterial Hydrogel for Skin Care

Min Wang,
Feng Yang,
Hao Luo
et al.

Abstract: The development of moisturizing, antibacterial, and biocompatible multifunctional hydrogels is essential to protect skin and promote skin defects recovery. Gelatin has admired potential to be applied for skin care as a hydrogel in virtue of its hydrophilic biocompatible and biodegradable properties. In this study, triclosan-grafted gelatin and photo-cross-linkable methacrylated gelatin were synthesized and then combined to construct the semiinterpenetrating network and antibacterial hydrogels with the aid of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Wang and colleagues developed a TCS‐grafted gelatin and GelMA composite biomaterial (TGM) crosslinked by LAP (0.2% wt/vol) with 405 nm violet–blue light. 70 The authors describe the material as having moisturizing properties and demonstrated antimicrobial efficacy against a variety of pathogens in vitro due to the TCS‐grafted component. Interestingly, when tested in vivo in Sprague Dawley rats, in situ photoactivated TGM exhibited a slight but significant acceleration of closure within 14 days of full‐thickness wounding, but gelatin‐GelMA demonstrated no benefit, suggesting TCS grafting provided added benefit.…”
Section: Visible Light‐activated Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and colleagues developed a TCS‐grafted gelatin and GelMA composite biomaterial (TGM) crosslinked by LAP (0.2% wt/vol) with 405 nm violet–blue light. 70 The authors describe the material as having moisturizing properties and demonstrated antimicrobial efficacy against a variety of pathogens in vitro due to the TCS‐grafted component. Interestingly, when tested in vivo in Sprague Dawley rats, in situ photoactivated TGM exhibited a slight but significant acceleration of closure within 14 days of full‐thickness wounding, but gelatin‐GelMA demonstrated no benefit, suggesting TCS grafting provided added benefit.…”
Section: Visible Light‐activated Materialsmentioning
confidence: 99%
“…Interestingly, when tested in vivo in Sprague Dawley rats, in situ photoactivated TGM exhibited a slight but significant acceleration of closure within 14 days of full‐thickness wounding, but gelatin‐GelMA demonstrated no benefit, suggesting TCS grafting provided added benefit. 70 In another group, Wang et al adapted LAP chemistries (0.5% wt/vol) to investigate hydrogels with additional adhesive properties by functionalizing the proadhesion molecule DOPA onto GelMA. 71 The group further modified their hydrogels by loading mesenchymal stem cell extracellular vesicles (EVs) into their hydrogel to impart prohealing angiogenic and wound motility properties.…”
Section: Visible Light‐activated Materialsmentioning
confidence: 99%
“…Gelatin, a protein extracted from animal connective tissue, has good biocompatibility and biodegradability, making it an ideal material for the preparation of biomedical materials. 13,14 Firstly, gelatin possesses excellent bio-adhesion properties that promote cell attachment and proliferation, contributing to tissue repair and regeneration. 15,16 Secondly, gelatin exhibits excellent biocompatibility with human tissues, avoiding any immune reactions or rejection.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Secondly, gelatin exhibits excellent biocompatibility with human tissues, avoiding any immune reactions or rejection. 14 Additionally, gelatin exhibits good biodegradability, eliminating the need for secondary surgical procedures. 17 Therefore, gelatin has a wide range of applications in the elds of tissue engineering, drug delivery systems and trauma repair.…”
Section: Introductionmentioning
confidence: 99%
“…The well-suited backbone of gelatin offers superb biocompatibility, biodegradability, and natural abundance that comes at meagre price. , Despite these advantages, gelatin lacks cohesion and interfacial adhesion strength, which could be tuned through modifications of surface functionalities . Physical mixing with tannic acid/PEG, photo-cross-linking with thiol/acrylate, cryo-polymerization, and reaction with transglutaminase are reportedly used to enhance adhesion and cohesion of gelatin. Chemical cross-linking with formaldehyde and glutaraldehyde in resorcinol has been found to enhance the bonding strength of gelatin-resorcin-formalin (GRF) and gelatin-resorcin-glutaraldehyde glues. , However, toxicological implications arise from the release of the aldehydes upon degradation of the bioadhesive.…”
Section: Introductionmentioning
confidence: 99%